Promote pa more! promoting maintenance and control of hypertension among patients in Barangay Galicia II, Mendez, Cavite - Balbedina, Janine Marie B.; Esparagosa, Jan Petros J.; Gutierrez, Meliz Iren Kaye R.; Tinaja, Charlene J.; Zaño, Basil John Fitzgerald P.
Galicia II is a barangay located in the fourth-class Municipality of Mendez, Cavite, with a total population of 2,092, and a total of 348 households. The Barangay Health Station (BHS) personnel consists of the Barangay Nurse, and four Barangay Health Workers (BHWs), with a BHW:household ratio of 1:87.